El crossfit y la recuperación muscular con CBD - Guilcapi Andrade, Pablo Andres (2024)
This research focuses on the application of cannabidiol (CBD) for muscle recovery in CrossFit athletes, a discipline that requires high intensity and endurance. The study explores whether CBD can offer significant benefits in terms of recovery and performance. The objective of the research is to determine the level of muscle recovery after the practice of CrossFit through the reactive CRP test where inflammation of the muscle tissues in the body will be evidenced. An experimental study was conducted for 12 weeks, with 8 CrossFit athletes evenly divided by gender in a CBD intervention group and a placebo control group. Inflammation was evaluated by the C-reactive protein test, which was used to determine the inflammation process that the athletes had. Athletes who received CBD reported a noticeable decrease in pain perception and inflammatory markers, compared to the control group. In addition, they showed faster and more effective recovery between training sessions. The study of the relationship between CRP and muscle recovery provides valuable information to better understand post-exercise recovery processes and to develop effective strategies to improve sports performance and promote muscle health. When analyzing the pre- and post-test results, a variability of the results obtained from the control group and the intervention group can be observed in their muscle recovery after CBD consumption. It is suggested to use other types of markers of inflammation when conducting future research.